(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the views of Eastern thinkers on the family and the historical formation and psychological essence of the multi-generational family form in the life of the peoples of Central Asia. The harmony of philosophical, religious and cultural approaches to the issue of family is expressed, in which the role of values ​​​​such as upbringing, kindness, solidarity and intergenerational respect in the human psyche is highlighted, the historical evolution of the family as a social institution, its impact on the stability of society and the formation of the individual are studied. Also, changes in family structure and intergenerational relations are analyzed in connection with socio-political factors that occurred in different periods. The ideas put forward in the article serve to interpret the family not only as an economic and legal unit, but also as an important factor in satisfying human psychological needs and personal development.